Theory Development of Genetic Counseling among Patient with Genetic Diseases - Henri Setiawan; Suhanda Suhanda; Elis Roslianti; Andan Firmansyah (International Journal of Nursing and Health Services (IJNHS), 2020)
Genetic Counseling is a communication process undertaken to address the issue of genetic diseases affected in the family. The basic concept of Selfcare is active awareness, while genetic counseling is passive awareness. The nursing theory is based upon the philosophy that all "patients wish to care for themselves". The objective of this study to sustain the theory development of genetic counseling related to Orem’s Selfcare theory following on from three relationship construction theories which include self care theory, self care deficit theory and nursing system theory. Genetic counseling is relevan with Orem’s selfcare theory as a gold standard to improve self care awareness, increase quality of life and reduce stress level among patients and families with genetic diseases.